Information System Sales of Cust Sistem Informasi Penjualan Aluminium, Kaca Dan Besi Custom Berbasis Website Study Kasus Family Glass And Stell - David Raynaldy; Endang Supriyati; Tri Listyorini (Fakultas Teknologi Informasi, 2023)
At Family Glass and Steel (FGAS) for ordering still using a manual system, namely by using books and paper, of course this will take time and also frequent errors in order recording and less efficient if it is crowded. There are also frequent out of stock because they forget the existing inventory so they are forced to refuse customer orders. So in need of a cashier system and a better stock of goods in order to improve performance. This system can run the ordering program as well as recording the stock of goods. This system is capable of recording product stock and running an ordering program. Using a website-based system, the waterfall method was used to create this system.